Vascular Mediators in Chronic Lung Disease of Infancy: Role of Endothelial Monocyte Activating Polypeptide II (EMAP II) - Lal, Charitharth Vivek (Birth Defects Res A Clin Mol Teratol, 2014)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease of prematurity. Over the years, the BPD phenotype has evolved, but despite various advances in neonatal management approaches, the reduction in the BPD burden is minimal. With the advent of surfactant, glucocorticoids, and new ventilation strategies, BPD has evolved from a disease of structural injury into a new BPD, marked by an arrest in alveolar growth in the lungs of extremely premature infants. This deficient alveolar growth has been associated with a diminution of pulmonary vasculature. Several investigators have described the epithelial/vascular co-dependency and the significant role of crosstalk between vessel formation, alveologenesis, and lung dysplasia’s; hence identification and study of factors that regulate pulmonary vascular emergence and inflammation has become crucial in devising effective therapeutic approaches for this debilitating condition. The potent antiangiogenic and proinflammatory protein Endothelial Monocyte Activating Polypeptide II (EMAP II) has been described as a mediator of pulmonary vascular and alveolar formation and its expression is inversely related to the periods of vascularization and alveolarization in the developing lung. Hence the study of EMAP II could play a vital role in studying and devising appropriate therapeutics for diseases of aberrant lung development, such as BPD. Herein, we review the vascular contribution to lung development and the implications that vascular mediators such as EMAP II have in distal lung formation during the vulnerable stage of alveolar genesis.